(untitled) (Canadian Medical Education Journal, 2021)
In March 2020, COVID-19 challenged health and educational systems across the country. The rapid reallocation of resources to ensure public safety had taken priority over educational obligations. Healthcare students were removed from clinical environments as their learning came to a grinding halt. While academic institutions were pivoting and transforming teaching and learning experiences, students responded to the pandemic with innovation, attending to gaps in patient care. As educators, we must understand how we can further support students and faculty to unleash innovative thinking during a crisis. To begin to address this educational need, academic institutions now have an opportunity to broaden the practice of education scholarship in accordance with best practices to nurture innovation and innovative thinking. What framework can aid us in this endeavor? In times of instability, Developmental Evaluation is an approach that can support the implementation of innovations within medical education. Using an example of an innovation in medical education, we offer six practical tips to begin to use Developmental Evaluation to support and enable learners and faculty in the creation of innovations and contribute to a broader definition of education scholarship.